2018
DOI: 10.1002/jemt.23007
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning capacity of octenidine as root canal irrigant: A scanning electron microscopy study

Abstract: The aim of this study was to assess the cleaning capacity of the octenidine hydrochloride (OCT) used as root canal irrigant by scanning electron microscopy (SEM) analysis. Sixty human unirradicular extracted teeth were randomly distributed in 6 groups (n = 10) according to irrigant solutions which were used during root canal preparation: G1, 0.1% OCT; G2, 2% chlorhexidine (CHX); G3, 2.5% sodium hypochlorite (NaOCl); G4, OCT + 17% ethylenediaminetetraacetic acid (EDTA); G5, 2.5% NaOCl + 17% EDTA and G6, distill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In recent research, OCT has been found to have lower cytotoxicity than CHX and NaOCl and to reduce the cytotoxicity of NaOCl without altering the free chlorine level when they are used together [ 13 14 ]. OCT can also be used with ethylenediaminetetraacetic acid (EDTA) for smear layer removal [ 15 ]. Its high antimicrobial properties, capacity to disinfect and clean dentin tubules and low toxicity profile make OCT a promising root canal irrigant [ 10 11 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent research, OCT has been found to have lower cytotoxicity than CHX and NaOCl and to reduce the cytotoxicity of NaOCl without altering the free chlorine level when they are used together [ 13 14 ]. OCT can also be used with ethylenediaminetetraacetic acid (EDTA) for smear layer removal [ 15 ]. Its high antimicrobial properties, capacity to disinfect and clean dentin tubules and low toxicity profile make OCT a promising root canal irrigant [ 10 11 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…OCT can also be used with ethylenediaminetetraacetic acid (EDTA) for smear layer removal [ 15 ]. Its high antimicrobial properties, capacity to disinfect and clean dentin tubules and low toxicity profile make OCT a promising root canal irrigant [ 10 11 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium hypochlorite (NaOCl) is the most widely used solution, owing to its antimicrobial/antibiofilm activity, and organic tissue dissolution capacity [ 5 6 7 ]. Additionally, since NaOCl cannot remove inorganic tissue, 17% ethylenediaminetetraacetic acid (EDTA) is recommended to address this limitation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%